In silico studies of OLED device architectures regarding their efficiency - Özdemir, Ali Deniz; Li, Fabian; Symalla, Franz; Wenzel, Wolfgang (Frontiers in Physics, 2023)
Simulations have become increasingly important to understand and design organic optoelectronic devices, such as organic light emitting diodes (OLEDs) and to optimize their performance by selecting appropriate materials and layer arrangements. To achieve accurate device simulations, it is crucial to consider the interplay between material properties, device architecture, and operating conditions and to incorporate physical processes such as charge injection, transport, recombination, and exciton decay. Simulations can provide insights into device bottlenecks and streamline optimization cycles, eliminating the need for physical prototyping and rationalizing OLED design. In this study, we investigated three heuristic OLED architectures and compared their quantum efficiency at different operation voltages. Our investigation focused on examining the effects of various layer arrangements on charge and exciton dynamics in OLED devices and establishing design principles for achieving high efficiency, which are consistent with experimental observations. Notably, we find that increasing the thickness of the emissive layer (EML) led to higher luminance efficiency, and that an emitter concentration of approximately 5% results in optimal performance. By using this model, it is possible to rapidly study the influence of many device parameters and explore a broad range of parameter and architecture space within a reasonable time-frame.